Turkish validity and reliability study of public attitudes towards epilepsy - Akturk, Ummuhan; Akalin, Yahya (Annals of Medical Research, 2021)
Aim: This study was conducted for the purpose of adapting the Public Attitudes Toward Epilepsy Scale (PATE) for the Turkish context and determining its validity and reliability. Material and Methods: This is a methodological research and conducted in a family health centre located in the eastern Turkey between February 2018 and September 2018. In this study, 268 individuals, who were older than 18 years and registered in a Family Health Centre, were reached. Results: The result of the KMO test was determined to be 0.783 and that of Bartlett’s test 1002.772, and both were observed to be significant at a level of p , 0.001. Conclusion: Our study determined that the Turkish version of the PATE has validity and reliability and can be used in Turkish society.